Preliminary Studies on the Antibacterial Mechanism of a New Plant-Derived Compound, 7-Methoxycoumarin, Against Ralstonia solanacearum - Han, Songting; Yang, Liang; Wang, Yao; Ran, Yuao; Li, Shili; Ding, Wei (Frontiers in Microbiology, 2021)
Ralstonia solanacearum (R. solanacearum) is one of the most devastating plant bacterial pathogens and leads to serious economic losses in crops worldwide. In this study, the antibacterial mechanism of 7-methoxycoumarin, a new coumarin antibiotic, was preliminarily investigated by the observation of symptoms and physical and biochemical analyses. The results showed that 7-methoxycoumarin significantly suppressed the bacterial growth of R. solanacearum, with the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) values of 75 mg/L and 175 mg/L, respectively. Electron microscopy observations showed that the bacterial cell membrane was destroyed after 7-methoxycoumarin treatment. Biofilm formation of R. solanacearum was significantly suppressed by 7-methoxycoumarin at concentrations ranging from 25 mg/L to 100 mg/L. Furthermore, virulence-associated genes of R. solanacearum including EpsE, HrpG and PopA, were significantly inhibited. The application of 7-methoxycoumarin effectively suppressed tobacco bacterial wilt progress in pot experiments, with relative control efficiencies of 83.61%, 68.78%, and 58.11% at 6 d, 8 d, and 10 d post inoculation with R. solanacearum, respectively.